Weeble: Enabling Low-Power Nodes to Coexist with High-Power Nodes in White Space Networks - Radunovic, Bozidar; Chandra, Ranveer; Gunawardena, Dinan (ACM CoNEXT, 2012)
One of the key distinctive requirements of white-space networks is the power asymmetry. Static nodes are allowed to transmit with 15dB-20dB higher power than mobile nodes. This poses significant coexistence problems, as high-power nodes can easily starve low-power nodes. In this paper, we propose Weeble, a novel distributed and state-less MAC protocol that solves the coexistence problem. One of the key building block is an adaptive preamble support, an add-on to the PHY layer that allows high-power nodes to detect a low-power transmission even when the difference in transmit power is as high as 20dB. The other key building block is a MAC protocol that exploits the adaptive preambles functionality. It implements a virtual carrier-sensing and automatically adapts the preamble size to optimize network performance. We extensively evaluate our system in a test-bed and in simulations. We show that we can prevent starvation of low-power nodes in almost all existing scenarios and improve the data rates of low-power links several-fold over existing MACs, and as a trade-off we decrease the throughput of the rest of the system by 20%-40%.